Теракотові статуетки римських воїнів з Північно-Західного Причорномор'я - Савельєва, К.С.; Савельєв, О.К. (Археологія, 2012)
Публікується добірка теракот, що представляють римських воїнів. Рассмотрены статуэтки с изображением воина в римской военной амуниции, найденные в Ольвии и ее округе (Козырское городище), Тире и Никонии. Особенность конструкции статуэток (подвесные ноги) указывает на их использование в культовой практике. Исследователи связывают их с культом Митры. Подтверждением этому служат изображения на щитах воинов, аналогии которым известны среди материалов митреумов. На основании типологического сходства статуэток из СевероЗападного Причерноморья и Малой Азии делается предположение о заимствовании иконографической схемы из Малой Азии. Considered are statuettes depicting soldiers in the Roman military ammunition found in Olbia and its suburbs (Kozyrka hillfort), Tyras, and Nikonis. The peculiarity of the statuettes structure, namely, the hanged legs, indicates that they were used in cultic practice. Scholars relate them to Mithras cult. It is confirmed by the depictions on the soldiers’ shields which have analogies among the materials from the Mithraeums. Based on the typological likeliness of the statuettes from the northwestern coast of the Black Sea and Asia Minor, the assumption is made about the adoption of iconographic scheme from Asia Minor.